APPLICATION OF TECHNOLOGY IN EDUCATION: AN INNOVATIVE LITERATURE REVIEW - Muhammad Arsyad; Abdul Wahab Syakhrani (CV. ADIBA AISHA AMIRA, 2025)
This literature review examines the application of technology in education and how these innovations affect teaching and learning. The research shows that technology has the potential to increase the accessibility and flexibility of education, reduce educational disparities, and provide a more interactive and personalised learning experience. However, the adoption of technology in education requires adequate infrastructure, technology competency training for teachers, and attention to student privacy and data security. In addition, challenges such as the risk of distraction, cyberbullying and technology dependency also need to be addressed through appropriate policies and regulations. With adequate support and a wise approach, technology can be an important tool in improving the quality of education and learning.